Natural mouthwash of sarang banua leaves (Clerodendrum fragrans Vent Willd) extractas a healthy solution during the covid-19 pandemic - Julianse Lydia Nababan; Titin Evania Manalu; Ratu Nurul Aulia; Anna Lestari; Angga Koswara Malau; Murniaty Simorangkir (Pascasarjana Universitas Negeri Medan, 2021)
The spread of the COVID-19 virus has shaken the world. The application of Clean and Healthy Living Behavior (CHLB) is the best effort to prevent the transmission of the Covid-19 virus. Maintaining oral and dental hygiene can improve health, especially during the COVID-19 pandemic. Sarang Banua (Clerodendrum fragrans Vent Willd) is a local plant of North Sumatra, containing secondary metabolites of alkaloids, steroids, flavonoids, triterpenoids, saponins, tannins, and quinones that have bioactivity such as antibacterial and antioxidant. The preparation of Sarang Banua mouthwash (SABANA) made from the extract of the sarang banua leaves with a concentration of 0.5 grams in 100 ml of preparation (0.5%) has been formulated, evaluated by organoleptic, pH and antibacterial test. The results of organoleptic and pH tests showed that SABANA mouthwash preparations were brown and slightly cloudy, tasted very distinctive, fresh, and eliminated bad breath with a pH of 7 in accordance with quality standards. About 70% of the panelists stated that they really liked the color, aroma, taste and appearance of SABANA mouthwash preparations. The results of antibacterial test against the oral bacteria Streptococcus mutans ATCC (25175) showed that 0.5% and 0.75% of the oral antibacterial mouthwash was found to be effective as oral antibacterial with an average inhibition zone diameter of 16.55 and 16.9 mm. Through the activities of the Student Creativity-Entrepreneurship Program, SABANA mouthwash have been produced and marketed in the local as well as outside the city by online and offline-shop and have the opportunity to develop into a new entrepreneur. Keywords: Mouthwash, Clerodenrum fragrans Vent Willd, antibacterial, streptococcus mutans